Can production subsidies foster export activity? Evidence from Chinese firm level data - Sourafel Girma; Yundan Gong; Holger Görg; Zhihong Yu (Centre for Economic Policy Research (CEPR), 2007)
Using a unique firm level data set from the Chinese manufacturing sector, this paper analyses the impact of production subsidies on firms' export performance. It documents robust evidence that production subsidies stimulate export activity, although this effect is conditional on firm characteristics. In particular, the beneficial impact of subsidies is found to be more pronounced amongst profit-making firms, firms in capital intensive industries and those with previous exporting experience. Compared to firm characteristics, the extent of heterogeneity across ownership structure (SOEs, collectives and privately-owned firms) proves to be relatively less important.
Keywords: F1; O2; P3; 330; Außenhandelswirtschaft; Exportindustrie; Subvention; Wirtschaftspolitische Wirkungsanalyse; Exporthandel; China